Austerity, the state and common sense in Europe: A comparative perspective on Italy and Portugal. (December 2021) - Alves de Matos, Patrícia; Pusceddu, Antonio Maria
In this article, we examine the making of austerity as common sense, located at the intersection of state interventions and the everyday practices and moral logics through which austerity emerges as an acceptable livelihood possibility for individuals, households and communities. Our argument is based on a comparative analysis of austerity in Italy and Portugal, with a focus on popular austerities among working-class households in two post-industrial towns. With the aim of addressing the conundrum of the pervasiveness of austerity, we emphasise the relevance of Gramsci's notion of common sense to expand the anthropological theorisation of austerity as a hegemonic project combining coercion and consent, capable of reconfiguring the state, and as a field of contradictions integral to the very making of common sense. We argue that austerity regimes become operative through the deployment of institutional coercive practices, moral arguments and the ideological co-optation of historical legacies of austerity embodied by ordinary people in their livelihood praxis.